Origin, development and influence of printing - Noyes, Fannie Gertrude (My University, 1899)
Introduction: “ ‘ Tis to the pen and press we mortals owe all we believe and almost all we know. Printing has been defined as “the act, art or practice of impressing letters, characters, or figures on paper, cloth, or other material.” Before printing was invented, all books were written by hand, there being several different kinds of writing employed, as the nature or purpose of the book differed. One kind was called the book hand, and was employed for legal, theological and devotional books. The church hand was used in works on the Bible, and other works of like nature used in the church or in private worship. The letter hand was employed in public writings in the nature of letters, while for charts, deeds, etc., the court hand was used. The first attempt at printing was long before the fifteenth century. –Pictures and engravings being the first crude result.
Citation: Noyes, Fannie Gertrude. Origin, development and influence of printing. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Hand Press; Treadle Press; Power Press; Theses; Manuscripts (documents)